Загальна характеристика адміністративно-правового статусу Департаменту міграційної поліції Національної поліції України - Магдалюк, В. І.; Mahdaliuk , V. I. (Право і суспільство. - 2023. - № 5. - С. 115-119, 2023)
Надано характеристику адміністративно-правовому статусу Департаменту міграційної поліції Національної поліції України. Визначено адміністративно-правовий статус як загальну категорію. Окреслено систему адміністративно-правового статусу державних органів, зокрема Департаменту міграційної поліції Національної поліції України. Встановлено сутність елементів адміністративно-правовому статусу Департаменту міграційної поліції Національної поліції України.

The author emphasized the need to clarify the content of the administrative and legal status of the Migration Police Department of the National Police of Ukraine, given its theoretical and practical significance. Thus, the purpose of the article is to provide a description of the administrativelegal status of the Migration Police Department of the National Police of Ukraine, in connection with which the following tasks were set: 1) definition of the administrativelegal status as a general category; 2) outline of the system of administrative and legal status of state bodies, in particular the Migration Police Department of the National Police of Ukraine; 3) outline the essence of the elements of the administrative and legal status of the Migration Police Department of the National Police of Ukraine. Thus, the administrative and legal status of the Migration Police Department of the National Police of Ukraine represents a certain established system, which consists of a number of constituent elements: 1) the purpose of creation and operation, which consists in the implementation of state policy in the field of combating illegal migration; 2) tasks, the main ones of which are: preventing and combating violations of migration legislation, as well as ensuring the provision of (administrative) services in the field of migration (registration, issuance, exchange of a passport of a citizen of Ukraine; acquisition, acceptance and renewal of Ukrainian citizenship; processing of documents for departure abroad, including the corresponding passport; recognition as a refugee or a person in need of additional or temporary protection; issuance of a certificate for return to Ukraine, etc.); 3) powers (normative, organizational, control, anti-corruption, administrativedelict, preventive, information-analytical, coordination and interaction with competent units of other state authorities and local self-government); 4) functions (administrative; organizational; security; law enforcement; preventive; information, as well as interaction function) and other elements (guarantees of activity and responsibility).

Дана характеристика административно-правовому статусу Департамента миграционной полиции Национальной полиции Украины. Определен административно-правовой статус как общую категорию. Обозначена система административно-правового статуса государственных органов, в частности Департамента миграционной полиции Национальной полиции Украины. Установлена ​​сущность элементов административно правового статуса Департамента миграционной полиции Национальной полиции Украины.
General characteristics of the administrative and legal status of the Department of Migration Policy of the National Policy of Ukraine
Keywords: адміністративно-правовий статус; administrative and legal status; административно-правовой статус; Департамент міграційної поліції; Migration Police Department; Департамент миграционной полиции; Національна поліція України; National Police of Ukraine; Национальная полиция Украины; адміністративні послуги; administrative services; административные услуги; повноваження; powers; полномочия